PENGARUH SISTEM PENGAPIAN CDI AC DAN DC TERHADAP KADAR GAS BUANG CO,HC DAN KONSUMSI BAHAN BAKAR PADAMESIN 110 CC - MUNTHE, IMMANUEL (JTIK (Jurnal Teknik Informatika Kaputama), 2019)
Motorbikes are the most effective means of transportation for the people of Indonesia, in addition to being affordable motorbikes can be used in a variety of road terrain. The main purpose of this study is to compare the performance of the DC CDI ignition system and the CDI AC ignition system in terms of fuel efficiency in comparing motorbikes DC CDI ignition system performance and CDI AC ignition system in terms of HC and CO gas emissions produced on motorbikes The method used to obtain the data needed to support this research is to conduct research with experimental literature study methods many authors use various supporting factors / input and supporting books related to the title discussed, where this study aims to compare the performance of the DC CDI ignition system and the AC CDI ignition system in terms of fuel efficiency and exhaust emissions produced on motorcycles. this study There are performance differences between magneto type ignition (CDI AC) and battery ignition (CDI DC) when viewed from CO and HC emissions on a 110 cc motorbike at 1000 rpm, 1500 rpm and 2000 rpm CDI AC generates more Emissions great compared to DC CDI at all engine rpm levels.